Study of Clinico-angiographic profile, Risk Factors and procedural outcomes in patients undergoing Coronary Angioplasty in Dhulikhel Hospital - Pathak, Surya Raj; Koju, Rajendra Prasad; Bhattarai, Nishan; Humagain, Sanjaya; Mehta, Ram Kumar; Pathak, Sujan (Nepalese Heart Journal, 2025)
Background and aim: Coronary Angioplasty is the preferred method of revascularization in Acute ST Elevation Myocardial Infarction (STEMI) and selected cases of Non- ST Elevation Myocardial Infarction (NSTEMI) and chronic coronary syndrome (CCS). This study was aimed to evaluate clinical and angiographic profile and procedural outcomes in patients undergoing percutaneous coronary intervention (PCI) at Dhulikhel Hospital, Nepal. Methods: This is a retrospective, observational, single center study conducted at Dhulikhel Hospital, Kathmandu University Hospital, Kavre, Nepal. All patients who underwent PCI for Acute Coronary Syndrome (ACS) and CCS in our hospital between April 1st, 2022 to March 31st, 2024, were included in the study. Data including clinical and angiographic profile, procedure and periprocedural complications, and in-hospital outcomes of these patients were analyzed. Results: A total of 189 patients (mean age 62.39 ±11.05 years) with 57.14% males and 42.85% females were included in the study. Hypertension and smoking were the most common risk factors, present in 79.36% and 76.19% patients respectively. Diabetes mellitus and dyslipidemia were observed in 47.62% and 35.45% patients respectively. STEMI ACS was the most common mode of presentation in 51.85% followed by NSTEMI in 32.80% and stable angina in 15.34%. Single Vessel Disease (SVD) was most common angiographic pattern, observed in 50.79% of patients, followed by Double Vessel Disease (DVD) in 63 patients (33.33%), and Triple Vessel Disease (TVD) in 30 patients (15.87%). Left anterior descending artery (LAD) was the most frequently involved vessel (63.49%). Elective PCI was performed in 53.96% and Primary PCI was done in 46.06 % patients. Radial route was used in the majority (90.47%) cases. Drug eluting stents were deployed in all the cases. Periprocedural complications occurred in 22.75%. There were 3 deaths, all after Primary PCI accounting for in-hospital mortality rates of 1.58%. Conclusion: This study provides an overview of the salient features of Coronary Artery Diseases and the characteristics of PCIs performed with their outcomes in a semi-urban tertiary care center of Nepal. This study shows that PCI done in resource- limited settings like Nepal is also safe, effective and has low in hospital mortality and complications, which is comparable to High-income countries.